Parent and Professional Collaboration in the Assessment Process - Squires, Jane; Waddell, Misti; Funk, Kristin; Macy, Marisa (Journal of Intellectual Disability - Diagnosis and Treatment, 2013)
Partnering with families to administer and interpret assessments for preschool children with disabilities is a cornerstone of effective early childhood practice. Parent-professional partnership in the assessment process encourages effective intervention practices, including targeting of appropriate goals and using strategies based on family cultural and daily practices. An assessment approach that focuses on collaborative practices between professionals and parents of young children with cognitive and other developmental delays is presented. Two strategies shown to provide a common language for parent and professional communication and facilitate cooperation between professionals and parents are described. Parent-completed developmental screening tests and parent assistance with completion of curriculum-based assessments are also discussed in the context of a tiered approach to intervention. A case study is presented to illustrate these strategies in practice.